Adoptive Immunotherapy With Engineered iNKT Cells to Target Cancer Cells and the Suppressive Microenvironment - Delfanti, Gloria; Dellabona, Paolo; Casorati, Giulia; Fedeli, Maya (Frontiers in Medicine, 2022)
Invariant Natural Killer T (iNKT) cells are T lymphocytes expressing a conserved semi-invariant TCR specific for lipid antigens (Ags) restricted for the monomorphic MHC class I-related molecule CD1d. iNKT cells infiltrate mouse and human tumors and play an important role in the immune surveillance against solid and hematological malignancies. Because of unique functional features, they are attractive platforms for adoptive cells immunotherapy of cancer compared to conventional T cells. iNKT cells can directly kill CD1d-expressing cancer cells, but also restrict immunosuppressive myelomonocytic populations in the tumor microenvironment (TME) via CD1d-cognate recognition, promoting anti-tumor responses irrespective of the CD1d expression by cancer cells. Moreover, iNKT cells can be adoptively transferred across MHC barriers without risk of alloreaction because CD1d molecules are identical in all individuals, in addition to their ability to suppress graft versus host disease (GvHD) without impairing the anti-tumor responses. Within this functional framework, iNKT cells are successfully engineered to acquire a second antigen-specificity by expressing recombinant TCRs or Chimeric Antigen Receptor (CAR) specific for tumor-associated antigens, enabling the direct targeting of antigen-expressing cancer cells, while maintaining their CD1d-dependent functions. These new evidences support the exploitation of iNKT cells for donor unrestricted, and possibly off the shelf, adoptive cell therapies enabling the concurrent targeting of cancer cells and suppressive microenvironment.